2013
DOI: 10.1063/1.4802794
|View full text |Cite
|
Sign up to set email alerts
|

Composition-dependent dielectric and energy-storage properties of (Pb,La)(Zr,Sn,Ti)O3 antiferroelectric thick films

Abstract: 1.8 -μm-(Pb0.97La0.02)(Zr0.95−xSnxTi0.05)O3 antiferroelectric thick films with orthorhombic (x = 0.05 and 0.25) and tetragonal (x = 0.40) structure were deposited on platinum-buffered silicon substrates by using a chemical solution way. All the films had a uniform microstructure with pure perovskite phase. With increasing x value, dielectric constant and critical electric breakdown field of the thick films were gradually increased, while their saturated polarizations were decreased. As a result, their maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(94 citation statements)
references
References 13 publications
3
91
0
Order By: Relevance
“…For instance, the Pnma state in ABO 3 perovskites is known to possess antipolar motions of its A cations and recent studies found that it can also adopt the double polarization-vs.-electric field hysteresis loop in some materials 13,14 that is characteristics of antiferroelectrics 15 -therefore suggesting that Pnma states in some perovskites can hold promise towards the design of energy storage devices with high energy densities and efficiencies. [16][17][18][19][20][21][22] Interestingly, all the aforementioned works on trilinear energetic couplings have been aimed at revealing and understanding resulting static properties. In other words, the effect of these original trilinear couplings on dynamics have been left out so far and are thus basically unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Pnma state in ABO 3 perovskites is known to possess antipolar motions of its A cations and recent studies found that it can also adopt the double polarization-vs.-electric field hysteresis loop in some materials 13,14 that is characteristics of antiferroelectrics 15 -therefore suggesting that Pnma states in some perovskites can hold promise towards the design of energy storage devices with high energy densities and efficiencies. [16][17][18][19][20][21][22] Interestingly, all the aforementioned works on trilinear energetic couplings have been aimed at revealing and understanding resulting static properties. In other words, the effect of these original trilinear couplings on dynamics have been left out so far and are thus basically unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Antiferroelectrics (AFEs) form a class of important materials that are currently receiving a lot of attention, mainly because they are promising candidates for obtaining high-density energy storage [1][2][3][4][5] . They are also fundamentally challenging and interesting, as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Antiferroelectrics display a field induced transition from antipolar to polar dielectric, and they have interesting properties such as the double hysteresis loop and large strains associated with it. These unique properties make antiferroelectric materials very attractive for technological applications involving high-energy supercapacitors [4][5][6][7][8], electrocaloric cooling [9], actuators [10], photovoltaic effects [11], and many other interesting dielectric phenomena. Very recently, experimental evidence of a novel four-state nonvolatile memory effect in antiferroelectrics was reported [12].…”
Section: Introductionmentioning
confidence: 99%